From Symbolic to Numerical Computing: The Story of Thinking Machines - Pelaez, Eloina (Research Centre for Social Science / University of Edinburgh, 1991)
The history of Thinking Machines and its computer, the Connection Machine, is a significant part of the general history of computing. Its history raises a whole number of issues central to the understanding of computing and its development. The aim of this paper is to look at some of these issues and thereby to throw light on the nature of technological development and transfer. The focus is on the transition of the Connection Machine from a university project to a commercial undertaking competing with the most advanced computers in the world. It is argued that such a move cannot take place without major changes in the technology involved, and that the shift from university to industry involves not a transfer but a transformation of technology.
Keywords: thinking machines; connection machine; history of computing